Cyberbullying Among Adolescents: The Influence of Different Modes of Inquiry - Brochado, Sandra (Journal of interpersonal violence, 2021)
The use of different modes of inquiry about interpersonal violence experiences may result in different frequency estimates. Thus, we measured the frequency and identified the factors associated with cyberbullying among urban school-going adolescents using different tools. Participants were enrolled at the four largest public schools in Porto for seventh- to 12th-grade students and were evaluated during the 2014-2015 academic year. We studied 2,624 adolescents (1,186 males and 1,438 females), 60% of all eligible students. Information under anonymity was collected at the school premises, using a self-administered questionnaire that comprised information on sociodemographic characteristics, school life, emotional well-being, the Internet use monitoring and cyberbullying experiences. Cyberbullying was assessed with two general questions (“Have you ever been a victim of cyberbullying?” and “In the last 12 months, have you been a victim of cyberbullying?) and using the Cyberbullying and Online Aggression Survey from the Centers for Disease Control and Prevention (CDC) that covers the last 30 days experience. The lifetime prevalence of cybervictimization was 7.6% and for the last 12 months 3.9%, similar in boys and girls, while the prevalence in the last 30 days was 38.2%, significantly higher in girls (43.1% vs. 33.3%). A statistically significant association of cybervictimization with negative emotional well-being and school bullying victimization experience was identified regardless of timing and the mode of ascertaining cyberbullying. Different measurement instruments resulted in different estimates of the prevalence of cyberbullying. Regardless of the instrument used, a strong association of cyberbullying involvement with negative emotional well-being in adolescents was observed.